2D finite element modeling of the non-collinear mixing method for detection and characterization of closed cracks. (December 2015) - Blanloeuil, P.; Meziane, A.; Bacon, C.
Abstract: The non-collinear mixing technique is applied for detection and characterization of closed cracks. The method is based on the nonlinear interaction of two shear waves generated with an oblique incidence, which leads to the scattering of a longitudinal wave. A Finite Element model is used to demonstrate its application to a closed crack. Contact acoustic nonlinearity is modeled using unilateral contact law with Coulomb׳s friction. The method is shown to be effective and promising when applied to a closed crack. Scattering of the longitudinal wave also enables us to image the crack, giving its position and size. Abstract : Highlights: Application of the non-colinear mixing technique to a closed crack. Finite Element Modeling of non-colineear mixing technique. The crack is modeled by an interface of unilateral contact with Coulomb׳s friction. The mechanisms of the scattering of the longitudinal wave are explained. Different parameters (position of sources, angle of incidence) are investigated.